EFFECTS OF 1-DOOR AND 2-DOOR OF 2-DECK HOOPNET TRAP ON CRUSTACEAN CATCHES AT PALABUHANRATU - Zulkarnain; Mokhammad Dahri Iskandar; Furqan; Ega Aldanita (Jurnal Penelitian Perikanan Laut (Albacore), 2026)
Potential crustacean resources in Palabuhanratu Bay are quite abundant, but traditional krendet traps are less effective because they lack protection and space dimensions. This study aims to compare the effectiveness of 1-door and 2-door of 2-deck hoopnet trap on crustacean catches. The experimental fishing method was conducted using 3 units of 1-door and 3 units of 2-door of 2-deck hoopnet traps for 20 trips in the waters of Palabuhanratu Bay. Data collected included the number, weight, and type of crustaceans caught. Data analysis used the Mann-Whitney non-parametric test to compare catches between the two trap types. The results showed that the 2-door had a higher number and weight of catches than the 1-door, with a production margin of 43.48% for number of fish and 69.49% for weight (kg). The dominant species was star crab (Portunus sanguinolentus), with more fingerlings caught in the 2-door of 2-deck hoopnet trap. Although statistical tests showed insignificant differences, the productivity of 2-door of 2-deck hoopnet traps tended to be better. In conclusion, the use of 2-door of 2-deck hoopnet traps is more effective in increasing crustacean catches and is recommended for use by fishers in the study area. Key words: 2-deck hoopnet, crustaceans, experimental fishing, traps